Proposals to improve the complementarity between civil engineering and social sciences in the higher education system of Ecuador based on national and international evidence (Latin-American Journal of Computing, 2021)
Based on evidence collected at the national and international level, this article proposes various mechanisms to improve the current complementarity between the fields of civil engineering and social sciences within the training of civil engineers under the framework of the higher education system of Ecuador. From an international mapping of relevant experiences in this area, and fieldwork conducted with mixed techniques within the higher education system, the article proposes concrete mechanisms through which the links between the social sciences and civil engineering can be strengthened. In a keyway, the field of Science, Technology and Society is proposed as a bridge, both in education and in the practice of these disciplines, to achieve this objective.